CLINIC CHARACTERISTICS OF CHRONIC HEPATITIS C WITH STEATOSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic Hepatitis C (CHC) is a major global health issue, with a substantial number of affected individuals developing hepatic steatosis. This study aims to analyze the clinical characteristics of CHC patients with hepatic steatosis, elucidating its impact on disease progression, liver function, and treatment response. Understanding these characteristics is crucial for optimizing therapeutic strategies and improving patient outcomes.